Experimental Study on Cohesiveness Characteristics of Raw Cement Ash at Moderate Temperature. (May 2017) - Han, Tao; Wang, Chang'an; Cao, Qi; Chen, Wufeng; Che, Defu
Abstract: Raw cement ash deposition in SP boilers gives rise to serious operation problems. In the present, mechanism of raw cement ash deposition is still unclear because the ash components, gas atmosphere and gas temperature are quite different from existing studies. The characteristics of cohesiveness of raw cement ash in moderate temperature were investigated in a lab-scale electric furnace. Three typical raw cement ashes were selected as samples, three base plates, including rough steel plate, smooth steel plate, organic glass plate were studied. Ball-impacting method was adopted to evaluate the cohesiveness of ash. Experimental results show that, the ash cohesiveness is mainly dependent on the components of ash, and the material property of base plate, while it exhibits little relationship with the roughness of the plate surface. Low-melting substances appear during ash deposition on steel plate. The results reveal that ferrum possibly has catalytic to some low-melting substances forming.